Acute Adrenal Insufficiency Associated with Acute Coronary Syndrome - Youngji Kim; Woojin Jung; Inkuk Cho; Seyeol Yang; Ho Han; Jung Hwan Park (Korean Journal of Critical Care Medicine, 2014)
Acute adrenal insufficiency (AAI) in acute coronary syndrome (ACS) patients is rare and may be frequently underestimated as simple ACS, since symptoms of AAI are nonspecific. Physicians should be fully aware of the possibility of occult AAI combined with ACS, if clinical suspicion is high. Herein, we report a rare case of a 67-year-old female patient with concomitant AAI and drug eluting stent fracture-induced ACS. To our knowledge, there have been no case reports of AAI associated with ACS in Korea.